Analysis of Biological Science Literacy Ability of Students’ Grade IX at Ujung Batu Junior High Schools - Ayu Andira; Suwondo Suwondo; Wan Syafi’i (FKIP - Universitas Riau, 2022)
The purpose of this research is to analyze the biological science literacy ability of students’ grade IX at Ujung Batu Junior High Schools. Students’ biological science literacy abilities are affected by many things, such as untrained students’ to solve characteristic questions such as the questions on PISA. This research used a descriptive method with a quantitative approach. The instrument used to capture students’ biological science literacy ability is a test. The research conducted at Ujung Batu Junior High Schools Accredited “A” population distributed in three schools with the population in this study was all the students in grade IX at Ujung Batu Junior High Schools in the 2019/2020 academic year. The Sampling technique used in this research is simple random sampling. The comprehensive scientific literacy score is 69.15, which is in the middle level. Based on aspects of scientific literacy (1) science content, amounted to 71.18 medium categories; (2) science process, 59.73 medium categories and (3) science context, 76.53 medium categories. The research conclusion is that there is a different capacity of students’ biological science literacy after using test questions on students’ scientific literacy ability.